Psychometric Properties of the Turkish Version of the University o Virginia Parent Low Blood Sugar Survey - ÇÖVENER ÖZÇELİK, ÇAĞRI (GALENOS YAYINCILIK, 2018)
Objective: The aim of this study was to produce and validate a Turkish version of the University of Virginia Parent Low Blood Sugar Survey (P-LBSS). The P-LBSS is used to assess parental fear of their diabetic children's hypoglycemia. Methods: Linguistic, content and face validity of the translated P-LBSS was tested. Afterwards, explanatory and confirmatory factor analyses were conducted in order to evaluate construct validity. Results: The sample included 390 parents of type 1 diabetic adolescents aged 12-17 years. Results of the factor analysis showed that the Turkish P-LBSS had 2 subscales (behavior and worry) as in the original. The Cronbach's alpha coefficient of the Turkish version of the total P-LBSS was found to be 0.803, and the value was 0.865 for the behavior and 0.790 for the worry subscales. Psychometric investigation of the Turkish version of P-LBSS indicated high reliability and good retestability, content and construct validity. Conclusion: The Turkish P-LBSS is a valid and reliable instrument to measure the fear of hypoglycemia experienced by parents of diabetic adolescents aged between 12-17 years in the TUrkish population.
Keywords: Type 1 diabetes mellitus; adolescent; validity; reliability; Turkey; DEPENDENT DIABETES-MELLITUS; PSYCHIATRIC-DISORDERS; YOUNG-CHILDREN; HYPOGLYCEMIA; FEAR; IDDM; YOUTHS; ADOLESCENTS